Oxidative shielding and the cost of reproduction. (12th March 2015) - Blount, Jonathan D.; Vitikainen, Emma I. K.; Stott, Iain; Cant, Michael A.
ABSTRACT: Life‐history theory assumes that reproduction and lifespan are constrained by trade‐offs which prevent their simultaneous increase. Recently, there has been considerable interest in the possibility that this cost of reproduction is mediated by oxidative stress. However, empirical tests of this theory have yielded equivocal support. We carried out a meta‐analysis to examine associations between reproduction and oxidative damage across markers and tissues. We show that oxidative damage is positively associated with reproductive effort across females of various species. Yet paradoxically, categorical comparisons of breeders versus non‐breeders reveal that transition to the reproductive state is associated with a step‐change reduction in oxidative damage in certain tissues and markers. Developing offspring may be particularly sensitive to harm caused by oxidative damage in mothers. Therefore, such reductions could potentially function to shield reproducing mothers, gametes and developing offspring from oxidative insults that inevitably increase as a consequence of reproductive effort. According to this perspective, we hypothesise that the cost of reproduction is mediated by dual impacts of maternally‐derived oxidative damage on mothers and offspring, and that mothers may be selected to diminish such damage. Such oxidative shielding may explain why many existing studies have concluded that reproduction has little or no oxidative cost. Future advance in life‐history theory therefore needs to take account of potential transgenerational impacts of the mechanisms underlying life‐history trade‐offs.